ZnO-morphology-dependent effects on the photovoltaic performance for inverted polymer solar cells - Lim, Ju Won; Hwang, Do Kyung; Lim, Keun Yong; Kang, Mingi; Shin, Sang-Chul; Kim, Hyun-Seok; Choi, Won Kook; Shim, Jae Won (Elsevier BV, 2017)
We report on the effects of zinc oxide (ZnO) morphology on the photovoltaic performance of inverted polymer solar cells (PSCs). Three different ZnO layers, fabricated from a sol–gel, nanoparticles (NPs), or nanorods (NRs), were employed as electron-collecting interlayers (ECIs) to compare their electrical, morphological, and optical properties in poly[4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-bA]dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]-thiophenediyl] (PTB7): [6,6]-phenyl-C70-butyric acid methyl ester (PC70BM)-based inverted PSCs. The work functions of all the ZnO layers were lower than or similar to the electron affinity of the acceptor, PC70BM, allowing the ZnO-coated indium tin oxide (ITO) substrates to act as efficient electron-collecting electrodes. The ZnO NRs induced not only stronger scattering effects but also more efficient electron collection than those of the devices with ZnO sol‒gel or NP ECIs, resulting in enhanced external quantum efficiency and, consequently, the highest power conversion efficiency (8.38±0.09%) under illumination (AM 1.5G, 100 mW/cm2). The optical effects of the ZnO NRs were confirmed by a finite-difference time-domain simulation.